Cystatin C predicts acute kidney injury and mortality in cirrhotics: A prospective cohort study. (19th October 2017) - Maiwall, Rakhi; Kumar, Awinash; Bhardwaj, Ankit; Kumar, Guresh; Bhadoria, Ajeet S.; Sarin, Shiv K.
Abstract: Background & Aims: Acute kidney injury is a frequent and ominous complication in cirrhosis. An episode of AKI damages the functional nephron mass, compromising the renal functional reserve. We aimed to study the incidence of AKI, probability of subsequent episodes, whether AKI itself predisposes to future AKI and the reliability of serum cystatin C(sCyC) as a biomarker in a prospective cohort of cirrhotics. Patients and Methods: Five hundred and thirty‐one cirrhotics without ongoing AKI were followed for development/resolution of AKI. Predictive models for AKI and mortality were developed and validated (Gr. A, Derivative cohort [n = 273], Gr. B, Validation Cohort [n = 258]). Results: 365 episodes of AKI occurred in 233 patients; yielding a mean of 1.56 episodes of AKI per patient. In Gr. A and B, 97 (35.5%) and 78 (30%) patients had prior AKI episodes and were predisposed to further attacks (Gr. A, HR 3.9, 95% CI 2.7‐5.6, Gr. B, HR 3.6, 95% CI 2.5‐5.4). AKI was thus an independent predictor of the development of new AKI( P  < .05) and this risk increased significantly with increase in the number of AKI episodes ( P  < .001). S.CysC but not s.Cr was an independent predictor of new AKI on multivariate analysis. " AKI‐Score " incorporating CysC; and the addition of Cyst into components of MELD, that is the " MELD‐Cystatin " score predicted the development of AKI and mortality, respectively, and performed significantly better than the MELD and CTP scores. Conclusions: An episode of AKI itself predisposes to subsequent attacks of AKI in cirrhotics. Scores incorporating CysC can accurately predict the development of AKI and mortality in these patients.